Corrosion and Small Sample Tensile Behavior of Ferritic/Martensitic Steel in Oxygen Saturated Lead-bismuth Eutectic - LI Shijiang1, GONG Aoxiang1, SUN Lu1, MA Yan1, QIN Bo2, LONG Bin2, TONG Zhenfeng1, (Yuanzineng kexue jishu)
Ferritic/martensitic (F/M) steels are potentially applied as structural materials in the lead cooled fast reactor, a promising fourth-generation reactor that adopts lead-bismuth eutectic (LBE) as coolant. However, the F/M steels normally suffer from a LBE sensitivity, showing a liquid metal embrittlement (LME) and liquid metal corrosion (LMC) when exposed to the LBE. Here in this paper, in order to study the compatibility of F/M steel in oxygen saturated LBE at different temperatures, the stress corrosion behavior of HT9 steel was conducted by slow strain rate tensile (SSRT) tests and corrosion tests in LBE at different temperatures. Comprehensive microstructural characterizations from atomic-scale examinations to micro-scale fracture analyses including HAADF-STEM, SAED, HRTEM-FFT, EBSD and SEM were performed to obtain the morphology and calibrate the crystallographic structure of tensile fracture and corrosion sample. The experimental results show that the total elongation of HT9 steel is 11.6% at 350 °C in oxygen saturated LBE, which is sensitive to the embrittlement of liquid LBE. However, when the temperature increases to 450-550 °C, the failure mode of the HT9 steel is dominated by the corrosion of LBE. The fracture mode changes from brittle fracture at 350 ℃ to plastic fracture above 350 ℃ and the total elongation is more than 2 times higher than that at 350 ℃. Through further characterization, it is found that the oxide layer is duplex, mainly composed of outer loose magnetite layer and inner chromite spinel layer when exposed HT9 steel in oxygen saturated liquid LBE at 350 ℃, while the magnetite layer cannot prevent the LBE to wet the HT9 steel matrix. Nevertheless, when exposed the sample in 550 ℃ LBE, a triplex oxide layer structure includes a thin Cr-rich and Fe-poor oxide layer (IOZ), the magnetite and chromite spinel layer are found near the interface of the HT9 steel matrix. The commonality is that the magnetite layer at different temperatures both has no effective protection to HT9 steel matrix, and even peels off from the matrix. Through the wettability tests of HT9 steel with LBE at different temperatures, it is found that the liquid LBE embrittlement is strongly temperature-dependent (350 °C), and the wetting of LBE to substrate may occur at an early stage of permeation to a shallow atomic depth at the contact interface. When the temperature increases above 450 °C, the wetting depth of LBE on the sample increases.